1997
DOI: 10.1097/00006123-199711000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Intramedullary Pressure in Syringomyelia: Clinical and Pathophysiological Correlates of Syrinx Distension

Abstract: The current study is the first to measure intramedullary pressure in a human disease. Evidence is presented that distended syringes are associated with varying levels of raised intramedullary pressure that can accentuate or induce neurological dysfunction by the compression of long tracts, neurons, and the microcirculation. Symptoms referrable to raised intramedullary pressure are potentially reversible by syrinx decompression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(32 citation statements)
references
References 37 publications
1
31
0
Order By: Relevance
“…Milhorat et al 26 (1997) measured the pressure in the interior of the syringomyelic cavity, and suggested that the distention would depended on different degrees of intramedullary pressure, causing lesion of long tracts, gray matter and microcirculation. The involvement of the anterior horns gives rise to fibrillation, fasciculation, muscular weakness and atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Milhorat et al 26 (1997) measured the pressure in the interior of the syringomyelic cavity, and suggested that the distention would depended on different degrees of intramedullary pressure, causing lesion of long tracts, gray matter and microcirculation. The involvement of the anterior horns gives rise to fibrillation, fasciculation, muscular weakness and atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Several pathophysiological factors are proposed to promote syringomyelia development: 1) reduction of subarachnoid compliance and accentuated pulse pressure in the cervical portion of the spinal subarachnoid space [16,43], 2) increased intrasyrinx pressure [36], 3) pressure gradients within the intramedullary extracellular fluid [23], 4) intrasyrinx fluid pulsation [9], 5) pulsation of the intramedullary arteries [51], and 6) patency of the central canal of the spinal cord [33]. However, because communication between the syrinx and fourth ventricle is usually not found in radiographic or post-mortem studies, it cannot play a role in pathogenesis of most cases of syringomyelia [34,43,45].…”
Section: Discussionmentioning
confidence: 99%
“…However, once myelopathy develops it is largely irreversible and it improves modestly, if at all, even if the syrinx is eliminated [25,43,54]. Factors other than syrinx diameter, such as intra-and extrasyrinx fluid pressures [16,36] and gliosis around the cavity, may play a role in the development of myelopathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2) This dynamic compression is a source of repetitive trauma, which results in vascular insufficiency of the affected spinal cord. 1,2) Marked improvements in rSCBF were observed immediately after drainage of the syrinx in patients with syringomelia, 22,38) based on laser Doppler flowmetry (LDF) during syrinx shunting. 22) LDF allows real-time monitoring of regional blood flow and can be used intraoperatively.…”
Section: Discussionmentioning
confidence: 99%